Gaze direction affects linear self‐motion heading discrimination in humans. Issue 8 (30th July 2013) - Ni, Jianguang; Tatalovic, Milos; Straumann, Dominik; Olasagasti, Itsaso
Abstract We investigated the effect of eye‐in‐head and head‐on‐trunk direction on heading discrimination. Participants were passively translated in darkness along linear trajectories in the horizontal plane deviating 2° or 5° to the right or left of straight‐ahead as defined by the subject's trunk. Participants had to report whether the experienced translation was to the right or left of the trunk straight‐ahead. In a first set of experiments, the head was centered on the trunk and fixation lights directed the eyes 16° either left or right. Although eye position was not correlated with the direction of translation, rightward reports were more frequent when looking right than when looking left, a shift of the point of subjective equivalence in the direction opposite to eye direction (two of the 38 participants showed the opposite effect). In a second experiment, subjects had to judge the same trunk‐referenced trajectories with head‐on‐trunk deviated 16° left. Comparison with the performance in the head‐centered paradigms showed an effect of the head in the same direction as the effect of eye eccentricity. These results can be qualitatively described by biases reflecting statistical regularities present in human behaviors such as the alignment of gaze and path. Given the known effects of gaze on auditory localization and perception of straight‐ahead, we also expect contributions from a general influence of gaze on the head‐to‐trunk reference frame transformations needed to bring motion‐related information from the head‐centered otoliths into a trunk‐referenced representation.